Metabolomic tissue signature in human non‐alcoholic fatty liver disease identifies protective candidate metabolites. (6th March 2014) - von Schönfels, Witigo; Patsenker, Eleonora; Fahrner, René; Itzel, Timo; Hinrichsen, Holger; Brosch, Mario; Erhart, Wiebke; Gruodyte, Auste; Vollnberg, Bernd; Richter, Klaus; Landrock, Andreas; Schreiber, Stefan; et al.
Abstract Background Non‐alcoholic fatty liver disease (NAFLD) is the most common chronic liver disorder in industrialized countries, yet its pathophysiology is incompletely understood. Small‐molecule metabolite screens may offer new insights into disease mechanisms and reveal new treatment targets. Methods Discovery (N = 33) and replication (N = 66) of liver biopsies spanning the range from normal liver histology to non‐alcoholic steatohepatitis (NASH) were ascertained ensuring rapid freezing under 30 s in patients. 252 metabolites were assessed using GC/MS. Replicated metabolites were evaluated in a murine high‐fat diet model of NAFLD. Results In a two‐stage metabolic screening, hydroquinone (HQ, pcombined = 3.0 × 10−4) and nicotinic acid (NA, pcombined = 3.9 × 10−9) were inversely correlated with histological NAFLD severity. A murine high‐fat diet model of NAFLD demonstrated a protective effect of these two substances against NAFLD: Supplementation with 1% HQ reduced only liver steatosis, whereas 0.6% NA reduced both liver fat content and serum transaminase levels and induced a complex regulatory network of genes linked to NALFD pathogenesis in a global expression pathway analysis. Human nutritional intake of NA equivalent was also consistent with a protective effect of NA against NASH progression. Conclusion This first small‐molecular screen of human liver tissue identified two replicated protective metabolites. Either the use of NA or targeting its regulatory pathways might be explored to treat or prevent human NAFLD.